Emotional fatigue, academic engagement, and satisfaction with studies during the return to post-pandemic university attendance - Mamani-Benito, Oscar; Esteban, Renzo Felipe Carranza; Huayta-Meza, Madeleine Victoria; Castillo-Blanco, Ronald; Chaparro, Josué E. Turpo; Morales Garcia, Wilter C. (Frontiers in Education, 2024)
The COVID-19 pandemic has significantly transformed various sectors, including higher education, exposing structural weaknesses and fostering the adoption of innovative teaching methods. This situation has created the need to understand how these changes have affected the academic satisfaction, academic engagement, and mental well-being of university students during the return to in-person education at universities. Methods: In this explanatory study, 1,321 Peruvian university students (52.1% women) aged between 17 and 35 years old (M=20.16, SD=3.04) participated. Participants were selected through a non-probabilistic convenience sampling method, recruited from the 3 regions of Peru (88.7% from the highlands; 76.2% from private universities), from faculties such as business sciences, humanities and education, engineering, and health sciences. Data were collected using the Emotional Exhaustion Scale (EES), the Brief Scale of Satisfaction with Studies (BSSS), and the Academic Engagement Scale (UWES S9). Results: The model relating the study variables showed an adequate fit: χ 2 (4) = 31.5, p < .001, CFI = .986, RMSEA = .072, SRMR = .017. The hypotheses were supported, showing the effect on satisfaction with studies both from emotional exhaustion, β = -.11, p < .001, and from academic engagement, β = .61, p < .001. Additionally, a 43% variance was explained in satisfaction with studies. Conclusion: This study evidence that, in the post-pandemic context, emotional exhaustion is a negative predictor of academic satisfaction, while academic engagement is positively associated with it. These findings suggest the need for educational strategies that mitigate emotional exhaustion and promote academic engagement to improve student satisfaction and well-being in the new educational normality.